2012
DOI: 10.1016/j.physa.2012.06.047
|View full text |Cite
|
Sign up to set email alerts
|

PageRank model of opinion formation on social networks

Abstract: We propose the PageRank model of opinion formation and investigate its rich properties on real directed networks of Universities of Cambridge and Oxford, LiveJournal and Twitter. In this model the opinion formation of linked electors is weighted with their PageRank probability. We find that the society elite, corresponding to the top PageRank nodes, can impose its opinion to a significant fraction of the society. However, for a homogeneous distribution of two opinions there exists a bistability range of opinio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 36 publications
1
50
2
Order By: Relevance
“…In the PROF model, the opinion of a node is updated by the weighted sum of neighbor nodes' opinions and the weight of the neighbor nodes are given by their PageRank (see the next section for details). It is found that a group of top influential elites in the networks (i.e., nodes with high PageRank) can impose their own opinion on a significant fraction of the considered networks [10]. The PROF model is also considered on Ulam networks [11], generated by the intermittency map and the Chirikov typical map, showing a similar behavior with the case of World Wide Web (WWW).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…In the PROF model, the opinion of a node is updated by the weighted sum of neighbor nodes' opinions and the weight of the neighbor nodes are given by their PageRank (see the next section for details). It is found that a group of top influential elites in the networks (i.e., nodes with high PageRank) can impose their own opinion on a significant fraction of the considered networks [10]. The PROF model is also considered on Ulam networks [11], generated by the intermittency map and the Chirikov typical map, showing a similar behavior with the case of World Wide Web (WWW).…”
Section: Introductionmentioning
confidence: 82%
“…The PageRank opinion formation (PROF) model, introduced in [10], takes into account a node influence in the pro-cess of opinion formation. In the PROF model, the opinion of a node is updated by the weighted sum of neighbor nodes' opinions and the weight of the neighbor nodes are given by their PageRank (see the next section for details).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameter Alpha reflects the relative importance of endogenous versus exogenous factors in the determination of centrality. PageRank vector is the right eigenvector with unit eigenvalue of the Google matrix constructed from the adjacency matrix of a given directed network [12]. PageRank vector is used by the Google search engine for an efficient ranking of web pages.…”
Section: Relationship Between Network Topology and Information Spreadingmentioning
confidence: 99%
“…In actual social networks, the interaction among agents is not always symmetrical. In [23], the authors proposed a PageRank model of opinion formation, in which connections between agents are weighted by a webpage ranking algorithm used by the Google search engine, i.e., PageRank probability. Similarly, in [24], opinion leaders with a strong convincing power were distinguished from ordinary people, and agents selected the weighted average of neighboring opinions.…”
Section: Introductionmentioning
confidence: 99%